The Political Dimension of the Ecological Crisis - Konstańczak, Stefan (Studia Ecologiae et Bioethicae, 2016)
A visible lowering of the level of social sensitivity to ecological problems will be a starting point for the considerations in this article. The author associates such a status quo with the activity of political powers for which solving ecological problems brings only costs and, quite often, compromises the interests of institutions sponsoring politicians. Owing to the influence of the media, social activity is steered by the authority elites mainly in the spheres easy to control. Ordinary citizens concerned about the state of the surrounding environment do not make the decisions of how to deal with the issues of ecological dangers; rather the process is dominated by political and economic lobbies. Immediate economic goals have completely overshadowed the concern about the future of our planet up to now. Therefore, in the conclusion, the author claims that new ideas and impulse are needed today to activate a disorientated society. And this impulse should emerge from environmental ethics.